Miguel y el dragon - Heck, Elisabeth, 1925-; Straube, Eckart (Madrid : Ediciones SM, 1983)
Miguel brings joy to the life of a very unhappy dragon who is looking for a friend.
Translation of: Der junge Drache.
"Primeros lectores"--P. [4] of cover.
Text in Spanish.
Keywords: Dragons -- Juvenile fiction; Friendship -- Juvenile fiction; Kindness -- Juvenile fiction; Dragons -- Juvenile fiction